FISCAL AND CONTROL FEATURES OF CUSTOMS AUTHORITY’S ACTIVITIES - BONDARENKO, Yevhen (Scientific journal «World of Finance», 2021)
Introduction. The deep and comprehensive political, economic and social processes taking place in modern Ukraine cause serious changes in the understanding of the role and importance of many industries and spheres of state activity that serve as the basis of Ukrainian society. Such spheres, the importance of which has been constantly growing in recent years, include the sphere of public relations related to the implementation of foreign economic activity. That is why, the study of the institutional mechanism of formation and implementation of customs policy, fiscal priorities of the customs service, the problems of control and administrative activities of customs authorities, their modernization is now becoming extremely acute and relevant.The purpose of the article is to determine the features and patterns of fiscal and control functions of customs authorities in Ukraine, analysis of indicators of revenue of the State Budget of Ukraine in terms of customs duties, monitoring ways to work out customs risks and outline ways to combat smuggling.Methods. Methods of dialectical analysis and synthesis, as well as methods of logical generalization, comparison and formalization are used in the research.Results. The essence and role of customs policy in the socio-economic development of the state are substantiated. Emphasis is placed on the peculiarities of the administration of customs payments and their mobilization to the budget. It is proved, that customs payments are important in the structure of budget revenues. The evaluation of the implementation of the planned indicators of fiscal activity of the State Customs Service of Ukraine was carried out. The risk factors of the customs space are identified and the methodical aspects of their development are outlined. Customs control plays a key role in preventing the smuggling of goods and detecting customs torts. Improving and digitalization of the control and verification work of customs authorities will help minimize fiscal losses, as well as, as summarized in the article - to improve the social and economic security of the state.Prospects. In the further scientific research, attention will be paid to the use of modern information technologies and technical means of customs control in the activities of the State Customs Service of Ukraine. The newest institutional paradigm of the customs space must take into account the digitalization of socio-economic processes.